Minimum Standard Theory to Practice in ECD Centers/Preprimary School - Thapa , Sabita (Kutumbha vani, 2025)
Abstract Early childhood represents a critical phase in a child’s physical, mental, social, and emotional development. The first five years shape logical thinking, interpersonal skills, and self management, making the role of caregivers, educators, and parents essential in creating opportunities for exploration and meaningful learning. Recognizing this, the Ministry of Education (MOE) in Nepal has developed a national ECD curriculum and minimum standards for ECD centers. This study examined 20 schools and 50 ECD/preschool classrooms in Gokarneshwor Municipality through direct observation, interviews, and key informant discussions, assessing their practices against MOE standards and the extent to which they meet children’s developmental needs. Findings reveal that 80% of educators are trained, with most being middle-aged women with children. Classrooms are generally child-friendly, with 85% furnished and decorated and 90% having outdoor spaces, though materials remain scarce. Strengths include sanitation (81.8%) and administration (80.6%), but only 17.7% of learning centers and 29.8% of language materials were available, with an overall 29% average provision of required resources. Both public and private ECD centers face space and furnishing challenges: government schools often have large but unfurnished rooms, while private schools operate in small residential buildings, limiting corners and activity areas. Teachers reported multiple challenges, including overcrowding, mixed-age classes, lack of assistant teachers, low pay, limited training, homework pressure, and insufficient play materials. Excessive classroom decoration occupies time but does not necessarily enhance learning. Unregulated preschools and inconsistent application of minimum standards exacerbate these issues. The study concludes that while infrastructure and sanitation needs are partly addressed, pedagogical enrichment, space management, parental awareness, and policy clarity remain urgent. Stronger integration of public and private preschools under MOE, regular monitoring, teacher support, and parental engagement are essential to ensure holistic child development and strengthen Nepal’s ECD sector.